MRI of the tumor microenvironment in radiotherapy: perfusion, hypoxia and metabolism - Matsuo, Masayuki (2014)
The tumor microenvironment is characterized by hypoxia, low pH, and high interstitial fluid pressure. Hypoxic regions in tumors with low pO(2) levels can result in resistance to radiotherapy causing local failure. It would therefore be desirable to non-invasively measure pO(2) levels in the tumor prior to, during, and after treatment to better customize therapy and follow treatment response. Several techniques used in pre-clinical and clinical studies to obtain pO(2) status of tissue such as dynamic contrast enhanced MRI (DCE-MRI), blood oxygen level dependent imaging (BOLD-MRI), and Electron Paramagnetic Resonance Imaging (EPRI) are reviewed. Furthermore, the ability to hyperpolarize specific metabolic substrates isotopically labeled with (13)C coupled with magnetic resonance spectroscopy enables non-invasive imaging of tissue metabolism such as glycolysis..